Uncovering Arabic Language Errors in Scientific Writing Undergraduate Thesis Context: An Analysis of Translation Aspect - Sa'adah, Fina; Inayah, Inayah; Ismail, Ismail; Muhammad Ahsanul Husna; Fikriyah, Dzakiyatul (Universitas Islam Negeri Jurai Siwo Lampung, 2025)
This study aims to identify and analyze Indonesian–Arabic translation errors in scientific writing among students of the Arabic Language Education Department at Walisongo State Islamic University. Specifically, it seeks to (1) examine the nature of written language translation, (2) evaluate the quality of student translations based on established criteria, and (3) classify common types of translation errors. Employing a qualitative, product-oriented research design, data were collected using purposive sampling from 39 students. The analysis focused on linguistic errors, with translation quality assessed through the criteria of accuracy, readability, and naturalness. The study identified the following types and frequencies of errors: letter-level errors (288), word structure errors (375), vocabulary errors (436), idiomatic or expression-related errors (336), and sentence-level errors (372). These findings suggest that Arabic language lecturers should consider developing idiomatic expression references, composition textbooks, and translation guides tailored to Indonesian–Arabic contexts. The department is encouraged to incorporate these insights into curriculum development, particularly for the courses “Indonesian–Arabic Translation” and “Academic Composition”.